THE DEVELOPMENT OF BOOK: APPROACHES, METHODS, AND LEARNING MODELS FOR LEARNING INDONESIAN IN PRIMARY SCHOOL - Apri Damai Sagita Krissandi (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2017)
This study aims to develop book approach, method, and model of learning Indonesian. This type of research includes research development (Research and Development). This study aims to develop and produce a specific product and test the validity of the resulting product. The development model used is a development model adapted from Borg and Gall development research steps (1983: 775). The development procedure is through the following stages: (1) determining the study of competency standards and learning materials, (2) needs analysis, (3) producing books, (4) product validation, and (5) revision of the final product. From the results of the recapitulation score, obtained the following details: 1) the score of the media expert is 4.7 with very good criteria; 2) score of Indonesian lecturers 4.8 with very good criteria; and 3) the mean of student validation score is 4.9 with very good criteria. Therefore, it can be concluded that the book approach, method, and model of learning Indonesian in primary school get an average score of 4.8 with the category of